Antecedents Affecting Purchase of Luxury Ayurvedic Skin Care Products - Pasricha, Diksha; Jain, Kokil (Indian Journal of Marketing, 2019)
Purpose: The study examined how the various underlying antecedents affect the purchase satisfaction and the re-purchase intention of luxury ayurvedic skin care products among young Indian consumers. Design/Methodology/Approach: A survey using the mall-intercept method was conducted in the Delhi-NCR region to understand the market of luxury ayurvedic skin care products with respect to the various dimensions defined in the literature. Data were collected from 203 respondents, and the proposed model was tested using partial least squares structural equation modeling (PLS-SEM) with Smart PLS v.3.2.7. Findings: Ideal self-congruity, sense of power, and product knowledge were observed as strong influencers of purchase satisfaction ; whereas, actual self-congruity had weaker influencing relationships. Product satisfaction of luxury ayurvedic skin care products was found to strongly influence the re-purchase intentions. Research Limitations/Implication: The findings were restricted to the young Indian consumers in Delhi-NCR, which cannot be generalized across the whole of India. Furthermore, only luxury ayurvedic skin care brands were considered. Originality/Value: Most studies have focused on luxury cosmetics and luxury skin care cosmetics; whereas, this study focused exclusively on luxury ayurvedic skin care cosmetic products. Self-congruity, sense of power, and product knowledge were added as antecedents towards purchase satisfaction and re-purchase intention of luxury ayurvedic skin care products.